Female dragons, Ctenophorus pictus, do not prefer scent from unrelated males - Jansson, N; Uller, T; Olsson, M (2005)
Female choice for genetic complementarity or unrelated males occurs in several vertebrate taxa, but only a few species per higher-order taxon have so far been studied. This is particularly the case in reptiles, where female choice traditionally has been considered to be less important than in most other vertebrates. Many species of reptiles use scent marking in relation to territory use and, consequently, females may use this information to avoid settling on genetically incompatible (e.g. related) males' territories. We tested the response of female Australian dragon lizards, Ctenophorus pictus, to pheromones from closely related and unrelated males. Contrary to predictions, females did not prefer to associate with scent from unrelated males. The reason for the lack of differential response to related and unrelated males could be explained by weak selection against inbreeding, high dependence on visual cues, female control over copulation, or post-copulatory female choice. Alternative hypotheses are discussed in relation to the biology of the species and lizard biology in general. © CSIRO 2005.